Incidence of Infective Endocarditis Among Patients With Tetralogy of Fallot - Eva Havers‐Borgersen; Jawad H. Butt; Morten Smerup; Gunnar H. Gislason; Christian Torp‐Pedersen; Mathis Gröning; Michael Rahbek Schmidt; Lars Søndergaard; Lars Køber; Emil L. Fosbøl (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2021)
Background Patients with tetralogy of Fallot (ToF) are considered at high risk of infective endocarditis (IE) as a result of altered hemodynamics and multiple invasive procedures, including pulmonary valve replacement (PVR). Data on the long‐term risk of IE are sparse. Methods and Results In this observational cohort study, all patients with ToF born from 1977 to 2018 were identified using Danish nationwide registries and followed from date of birth until occurrence of first‐time IE, emigration, death, or end of study (December 31, 2018). The comparative risk of IE among patients with ToF versus age‐ and sex‐matched controls from the background population was assessed. Because of rules on anonymity, exact numbers cannot be reported if the number of patients is <4. A total of 1164 patients with ToF were identified and matched with 4656 controls. Among patients with ToF, 851 (73.1%) underwent early surgical intracardiac repair and 276 (23.7%) underwent PVR during follow‐up. During a median follow‐up of 20.3 years, 41 (3.5%) patients with ToF (comprising 24 [8.7%] with PVR and 17 [1.9%] without PVR) and <4 (<0.8%) controls were admitted with IE. The incidence rates of IE per 10 000 person‐years were 22.4 (95% CI, 16.5–30.4) and 0.1 (95% CI, 0.01–0.7) among patients and controls, respectively. Moreover, PVR was associated with a further increased incidence of IE among patients with ToF (incidence rates per 10 000 person‐years with and without PVR were 46.7 [95% CI, 25.1–86.6] and 2.8 [95% CI 2.0–4.0], respectively). Conclusions Patients with ToF are associated with a substantially higher incidence of IE than the background population. In particular, PVR was associated with an increased incidence of IE. With an increasing life expectancy of these patients, intensified awareness, preventive measures, and surveillance of this patient group are decisive.